Pelangaran Outsourcing Yang Dapat Dikategorikan Sebagai Tindak Pidana Perdagangan Orang - Alexander Simon Pally (SASI, 2019)
This study discusses Outsourcing violations which can be categorized as Trafficking in Persons. In this writing, outsourcing workers employed need to get legal protection in accordance with the mandate of Article 27 paragraph (2) of the 1945 Constitution stating "Every citizen has the right to work and remuneration that is appropriate for humanity" and Article 28D paragraph (2) asserting that "every person has the right to work and receive compensation and fair and proper treatment in employment relations" outsourcing workers who work outside and / or exceed working hours, and the recruitment of the wrong workers need to be sanctioned as a form of protection for workers. Based on Article 65 paragraph (6) of Law Number 13 of 2003, this study uses the Normative Juridical research method which uses library legal materials and in the results of its research the researcher gets the implementation of the outsourcing system work relations occur, namely between labor, employer, and providers of labor or outsourcing companies. The Crime of Trafficking in Persons is possible to occur when from the process of recruitment of workers, appropriation of workers and remuneration of workers.